Potencial adaptativo de transcritos quiméricos gene-elemento de transposição em Drosophila melanogaster e D. simulans - Manfré, Bianca (2023)
Transposable elements (TEs), an important source of genetic variability due to their ability to move within the genome, are predominantly deleterious and neutral. However, when domesticated by the genome, TEs play a positive role in the evolution of organisms, leading to an increase in gene number and diversity and enriching gene regulation pathways. Identifying chimeric gene + TE transcripts is one way of investigating their domestication, which can be classified according to the TE insertion site in relation to the gene: transcripts TE-initiated -, TE-exonized and TE-terminated. To identify chimeric transcripts suggestive of domestication events, we analyzed transcriptomes from the ovaries of Drosophila melanogaster and D. simulans, from Gotheron (France, temperate climate) and São José do Rio Preto (Brazil, tropical climate), two strains from each location, exposed to Cold-Shock and Starvation stresses. The analysis was carried out using ChimeraTE, a pipeline capable of detecting chimeric transcripts in transcriptomes obtained by paired-end RNA-seq, and identified through genomic alignment. Differential expression analysis made it possible to identify the modulation of gene expression induced by TEs associated with the two types of stress. An average of 396 chimeric transcripts were identified in the D. melanogaster strains and 285 in the D. simulans strains, in 90% of which the TE was exonized. Approximately 1% of the genes produced chimeric transcripts, of which six were considered as potential adaptive cases because their expressions are apparently modulated by the TE insertions. Three genes were differentially expressed (DE) between the control and treatments: Paris, Sulf1 in D. melanogaster and GD24271 in D. simulans. The gene Paris, a with an upstream, polymorphic Burdock insertion (LTR, Gypsy superfamily), only in the Gotheron strains, is DE in only one of the strains under Cold-Shock. Sulf1, with an intronic, polymorphic insertion of Micropia (LTR, Gypsy superfamily), is a DE gene in the same strain as Paris, both under the Cold-Shock and Starvation stresses. The third gene, GD24271, which presented in all the D. simulans strains an upstream, polymorphic insertion of the G5A element (LINE, Jockey superfamily), but produced chimeric transcript, and was DE under Cold-Shock only in a European strain. Three other genes were DE when comparing the expression between temperate and tropical populations: CG5096 and CG42598 in D. melanogaster and GD24387 in D. simulans. The gene CG5096, with an upstream insertion of 412 (LTR, Gypsy superfamily), unique to a Gotheron lineage, exhibited higher expression in this population. On the other hand, the genes CG42598 in D. melanogaster, with an intronic insertion of gypsy4 (LTR, Gypsy superfamily), and GD24387, in D. simulans, with an upstream insertion of the INE-1 element (DNA, Helitron superfamily)̧ both with TE insertions common to all strains, showed greater expression in the Brazilian strains. In all these cases, the change in gene expression only occurred in strains that generated chimeric transcripts. These observations suggest a possible regulatory action of TEs, which in turn modulate the expression of adjacent genes. In situations where the change in expression of the Sulf1, Paris and GD24271 genes appears to have been activated by stress, the chimeric transcripts occurred only in strains native to the temperate region. These changes suggest an adaptive response to the cold, since survival in winter, with low temperatures and food restriction, is a challenge to be overcome by insect populations. Meanwhile, the changes in expression of the CG5096, CG42598 and GD24387 genes between strains from the two climatic regions, independent of the TE insertion, suggest adaptations to colonizing different habitats. In summary, these results illustrate how stress can induce the domestication of TE, in a way that reflects the adaptation and evolutionary history of the organisms.